Implementation of staff development program for Malaysian schools - Ab Samad, R.S.; Shahdan, A. (2008)
According to the National Commission on Teaching and America's Future (1996), staff development programs can be defined as ongoing learning opportunities made available to teachers through their school or school district. Notably, the staff development program is one of the effective ways to achieve world-class education. This paper will propose the best practices of Staff Development Program that are appropriate for schools, specifically in the Malaysian context. The focus of this paper is to discuss the six indicators that appear to be the contributing factor for the development of Malaysian teachers. To elaborate, the characteristics of the six indicators include practice and feedback; coaching and expert modelling; instructional leadership; whole school and administrative support; collegiality; and the quality of information presented and demonstrated. There are five important steps required in implementing the staff development program successfully, namely preparation, planning, training, implementation, and maintenance. Significantly, these steps are crucial for staff development program effectiveness.